Limited Attention in the Housing Market: Threshold Effects of Energy-Performance Certificates on Property Prices and Energy-Efficiency Investments - Rodolfo Sejas-Portillo; David Comerford; Mirko Moro; Till Stowasser (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We study the effects of limited attention on property prices and energy efficiency (EE) investments in the housing market. Using a novel dataset, we analyse over 5 million residential property sale transactions in England and Wales, each containing information about sale price, property and location characteristics, and a mandatory energy performance certificate (EPC). The EPC includes a continuous energy cost rating (SAP rating) which is mapped into seven colour-coded rating bands (ranging from green A to red G). Applying a Regression Discontinuity Design (RDD), we document significant price discontinuities at the rating band thresholds. We estimate that - holding the underlying SAP score equal - being in a higher rating band increases the final sale price of a property between 0.8% and 2.5% (2,000 and 6,625 based on average sale prices) depending on the threshold crossed. The presence of price discontinuities suggests that individuals are attentive to the simpler colour-coded rating band and partially inattentive to the more precise SAP rating. We present a simple model for estimating the degree of inattention and show that, for a given level of attention, rating bands reduce attention to the SAP rating by 25% on average. Importantly, the detected price discontinuities appear to influence market behaviour: Sellers whose property receives an EPC rating just below a threshold to the next-higher rating band are between 0.4% and 11% more likely to make last-minute EE investments before placing their property on the market. We discuss a number of recommendations of how to best leverage these threshold effects to improve policy design, which can be extended to other settings where the provision of simplified information creates reference thresholds.
Keywords: D12; D83; L15; R21; R31; Q48; 330; limited attention; heuristic decision-making; price discontinuities; housing market; anchoring and adjustment; energy policy; energy efficiency; energy performance certificates; EPC